Survival benefits of palliative gastrectomy for gastric cancer patients with liver metastasis: a population-based propensity score–matched cohort analysis - Ren, Bingyi; Yang, Yichen; Lv, Yi; Liu, Kang (Frontiers in Oncology, 2023)
Background and Aims: Palliative primary tumor resection (pPTR) can benefit colorectal cancer patients with liver metastasis. Whether pPTR benefiting gastric cancer (GC) patients with liver metastasis is still controversial. Methods: Data on patients with metastatic GC diagnosed between 2010 to 2019 was extracted from SEER database. Propensity score analysis with 1:1 matching was performed. The univariable and multivariable Cox proportional hazards regression models were used to explore prognostic factors. Kaplan-Meier methods was used to analyze survival outcomes. Results: Of 5692 GC patients with liver metastasis, 468 were included in the matched cohorts. The results showed that the median survival time was 6 months in the non-surgery groups and 14.5 months in the surgery groups (p < 0.001). Multivariable analysis showed that surgery was a protective prognostic factor for overall survival [hazard ratio (HR) = 0.416] as well as cancerspecific survival (HR = 0.417). Also, pPTR was only recommended for GC patients with isolated liver metastasis. Moreover, pPTR combined with chemotherapy brought the greatest therapeutic effect. Conclusions: pPTR benefits GC patients with isolated liver metastasis, and GC patients with liver metastasis receiving pPTR combined with chemotherapy had the best survival outcomes than any other therapeutic model.